Some magnetic resonance experiments on solids - Emeleus, T (1966)
Since the first observation of nuclear magnetic resonance (n.m.r.) in ferromagnetic cobalt (1), n.m.r. has been used extensively to study the electron-nucleus hyperfine interaction in magnetically ordered materials (2). This thesis describes an unsuccessful attempt to extend such studies to the magnetically ordered phases of terbium and holmium metals. Detailed calculations of the intensity of the predicted n.m.r. signal in terms of linewidth and electronic susceptibility at the n.m.r. frequency are given for the heavy rare earth metals gadolinium to thulium, and a comparison is made with europium and with iron, cobalt and nickel. With the exception of gadolinium, which has a closed 4f electrons shell configuration, the hyperfine interactions at 0°K in the heavy rare earth metals vary from ≐ 800 Mc/sec. in dysprosium to 6,500 Mc/sec. in holmium. These are an order of magnitude higher than in most magnetically ordered materials and we show that this, combined with relatively weak exchange interactions, is likely to lead to a very strong nuclear spin-spin coupling. The corresponding short spin-spin relaxation times and line broadening may make n.m.r. difficult to observe. A qualitative discussion of spin-lattice relaxation mechanisms shows that the spin-lattice relaxation times will probably be shorter than in the 3d transition metal ferromagnets. In a magnetically ordered material n.m.r. is excited indirectly through the electronic magnetisation and electron-nucleus hyperfine coupling, leading to enhancement of the oscillatory field exciting the n.m.r. We have measured as a function of temperature the combination | μ | + μ" = μR of the components of the complex permeability μ' -jμ" in crystal specimens of terbium and holmium metals and in a terbium polycrystal, in the region of the respective predicted n.m.r. frequencies. The results are used to elucidate the enhancement of n.m.r. in these metals, and it is shown that in the forromagnetic phases domain wall motion at the n.m.r. frequency is largely absent. Measurement of μR at ≐ 3,OOO Mc/sec. on a crystal of dysprosium metal in the temperature range 20°K to 280°K is also reported. In all cases peeks are found in μR at the magnetic ordering transitions and in the ordered phases μR varies from ≐ 1.2 to ≐ 5. Incidental to the permeability measurements, measurement of the d.c. resistivities of terbium, holmium and dysprosium crystals have been made throughout the temperature range 10°K to 280°K. The current flow In each case is at a specified angle between the c-axis and the basal plane. Resistivity measurements on a terbium polycrystal hove also been made from 77°K to 280°K. The results are consistent with the most reliable data of other workers. Qualitative measurement of microwave absorption at 3,000 Mc/sec. in a powder sample of terbium shows no peak at the ferromagnetic to antiferromagnetic ordering transition (≐ 220°K), and also that the microwave magnetic permeability at 77°K is considerably larger than in bulk terbium. Low frequency and d.c. susceptibility measurements confirm the absence of an ordering transition at 220°K, and show that ferromagnetism sets in at the normal Neel temperature (≐ 23O°K) and persists continually to low temperatures. Observation of microwave power absorption in the strained surface of a terbium single crystal also shows one magnetic ordering transition only, at 230°K. A continuous wave variable frequency spectrometer depending on a double modulation principle and partial saturation of the n.m.r., operating in either in the region of 3,000 Mc/sec. or 6,500 Mc/sec. (the terbium and holmium predicted n.m.r. frequencies) has been developed. This is capable of detecting a fractional change δQ/Q of 5xlO-5 in the quality factor Q of a coaxial cavity containing the specimen. In application to a search for n.m.r. in terbium and holmium crystals, the specimens formed the centre conductor of the cavity. The extent of the search made is 2954 to 3078 Mc/sec. at 77°K, and 2957 to 3010 Mc/sec. at 72°K in terbium, and from 5320 to 6570 Mc/sec. at ≐ 20°K in holmium. The measured permeability at the n.m.r. frequency is combined with the calculations of the n.m.r. absorption intensity and the measured spectrometer sensitivity to show that, subject to the necessary partial saturation conditions being fulfilled, no n.m.r. signal less than of order 10 Mc/sec, broad is present in the holmium, or less than of order 0.4 Mc/sec, in the terbium. These results are consistent with the estimated magnitude of the contribution to n.m.r. linewidth due to nuclear spin-spin coupling.